Characteristics of vestibular migraine, probable vestibular migraine, and recurrent vertigo of childhood in caloric and video head impulse tests - Zhang, Qin; Wu, Qiong; Chen, Jianyong; Wang, Xueyan; Zhang, Yuzhong; Liu, Shuyun; Wang, Lu; Shen, Jiali; Shen, Min; Tang, Xinyi; Mei, Ling; Chen, Xiangping; et al. (Frontiers in Neurology, 2022)
Objective Vertigo is very common in children, but the specific diagnosis and characteristics are not clear. The main objective of this study was to analyze the characteristics of caloric test (CT) and video head impulse test (vHIT) in vestibular migraine of childhood (VMC), probable vestibular migraine of childhood (PVMC), and recurrent vertigo of childhood (RVC), which can provide a reference value for their clinical diagnosis. Methods We selected VMC, PVMC and RVC patients under 18 years of age from the outpatient Department of Otolaryngology–Head and Neck Surgery between May 2021 and August 2022. All patients underwent vestibular function examinations, including eye movement recording CT and vHIT. CT results depended on whether both canal paresis and directional preponderance were under normal limits, and vHIT results depended on the gain values of vestibulo-ocular reflex. The results of both tests were analyzed according to the disease type. Results Among the 81 pediatric vertigo patients aged 5–17 years, 44 were females and 37 were males. According to the type of vertigo, 29 patients (25.80%) were diagnosed with VMC, 11 (13.58%) with PVMC, and 41 (50.62%) with RVC. The abnormal rates of the CT in VMC, PVMC, and RVC patients were 24.14%, 36.36%, and 17.07%, respectively. There was no significant difference in the abnormal rates among the three groups (P > 0.05). None of the patients showed abnormal vHIT results (all abnormal rates 0.00%). The abnormal CT rates were significantly higher than those of abnormal vHIT rates (P < 0.05). Conclusions VMC, PVMC, and RVC are more likely to be diagnosed by symptoms, as neither CT nor vHIT are specific to any conditions. Due to different clinical presentations of vertigo in pediatric patients, it is critical to further clarify the diagnosis with medical history and clinical characteristics.